2020
DOI: 10.1016/j.joms.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab, a Potent Interleukin-6 Receptor Inhibitor, Decreases Bone Resorption and Increases the Rate of Bacterial Infection After Tooth Extraction in Rats

Abstract: Purpose Our objective was to evaluate the influence of pretreatment with tocilizumab (TCZ) in bone healing after tooth extraction in rats. Methods Wistar male rats were equally divided into sham (ie, nonoperated), saline (both treated with 0.1 ml/kg saline), and six TCZ groups treated with 1, 2, 4, 8, 16, and 32 mg/kg TCZ (TCZ1 to TCZ32, respectively). Twenty-four hours after administration of vehicle or TCZ, exodontia of the first lower left molar was performed, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In summary, considering the nature of case reports like ours and the current lack of prospective studies, we can only assume causality between interleukin-6 inhibitors such as tocilizumab and MRONJ. With the promising future perspectives of tocilizumab use in immunoinflammatory diseases and in COVID-19 treatment, our clinical report as well as the research of Imaculada de Queiroz Rodrigues et al [ 31 ] and previous case reports showed that in the clinical setting, surgeons need to pay attention to side effects of tocilizumab, especially due to increased risk of postsurgical infection. This clinical case recommends a dental examination before prescribing tocilizumab as well as periodic dental checkups during treatment.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…In summary, considering the nature of case reports like ours and the current lack of prospective studies, we can only assume causality between interleukin-6 inhibitors such as tocilizumab and MRONJ. With the promising future perspectives of tocilizumab use in immunoinflammatory diseases and in COVID-19 treatment, our clinical report as well as the research of Imaculada de Queiroz Rodrigues et al [ 31 ] and previous case reports showed that in the clinical setting, surgeons need to pay attention to side effects of tocilizumab, especially due to increased risk of postsurgical infection. This clinical case recommends a dental examination before prescribing tocilizumab as well as periodic dental checkups during treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Recent scientific reports declare the intravenous administration of tocilizumab in the treatment of the COVID-19 related acute respiratory insufficiency with encouraging results [ 30 ], [ 31 ], [ 21 ], [ 22 ]. Due to an overproduction of proinflammatory cytokines and especially IL-6, a large number of COVID-19 affected patients in critical situation experience a “cytokine storm” [ 31 ]. This storm contributes to increased disease severity as well as aggravation of prognosis, and tocilizumab contributes to symptom improvement by reducing the IL-6 expression associated inflammation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations